2012
DOI: 10.1080/14719037.2012.657835
|View full text |Cite
|
Sign up to set email alerts
|

Performance Measurement and Performance Information in New Democracies

Abstract: This article explores the introduction of performance measurement tools in new democracies by presenting a qualitative study based on Estonian governmental documents and performance audits. A set of specific factors help to explain difficulties in introducing performance measurement tools in immature policy environments: instability, poor strategic planning and policy analysis, an implementation gap, uncritical and uninformed transfer of Western performance management initiatives. Although the authors recogniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Political pressures that enrol PM in impression management efforts can cause PM design to be unsupportive for its role in discharging accountability to external constituents (Chang, ) and can cause PM‐induced gaming (Bevan and Hood, ). These pressures, as well as turbulent policy environments and pre‐occupation with management fads can cause PM to be misaligned to public sector goals and organisational contexts (Milakovich, ; and Nõmm and Liiv, ). Volatile political support for PM can also cause under‐utilisation of PM information (Yang and Hsieh, ; and Hou, ), as can political and institutional pressures to conform to norms of economic rationality, especially if decoupled or loosely coupled PM systems are implemented (Johansson and Siverbo, ; and Torres et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Political pressures that enrol PM in impression management efforts can cause PM design to be unsupportive for its role in discharging accountability to external constituents (Chang, ) and can cause PM‐induced gaming (Bevan and Hood, ). These pressures, as well as turbulent policy environments and pre‐occupation with management fads can cause PM to be misaligned to public sector goals and organisational contexts (Milakovich, ; and Nõmm and Liiv, ). Volatile political support for PM can also cause under‐utilisation of PM information (Yang and Hsieh, ; and Hou, ), as can political and institutional pressures to conform to norms of economic rationality, especially if decoupled or loosely coupled PM systems are implemented (Johansson and Siverbo, ; and Torres et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Proponents of rational planning models attribute a number of benefits to their use, including the expectation that PSOs which have clear goals perform better (Andrews & Van de Walle, , p. 776), and that the first step in an organization's strategic planning process is to set goals. Accordingly it has been suggested that “… planning is a critical function for organizational development through achievement of the goals” (Jung & Lee, , p. 789); with performance information (as per Figure ) being used internally for better planning and externally for greater accountability (Nomm & Randma‐Liiv, , p. 862). Nomm and Randma‐Liiv () further suggest that internal uses of performance information should underpin benchmarks which inform future decisions and budget allocations.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Accordingly it has been suggested that “… planning is a critical function for organizational development through achievement of the goals” (Jung & Lee, , p. 789); with performance information (as per Figure ) being used internally for better planning and externally for greater accountability (Nomm & Randma‐Liiv, , p. 862). Nomm and Randma‐Liiv () further suggest that internal uses of performance information should underpin benchmarks which inform future decisions and budget allocations. This dovetails with observations that such information can improve decision‐making (de Lancer Julnes, , p. 58) and form an important element of good management (Van Dooren, , p. 21).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Estonian local governments have also followed the practice of lean state and public sector, fostered by the majority of Estonian governments since 1991 (Nõmm and Randma-Liiv, 2012;Tõnnison, 2006). Still, any rapid political and economic transformation in a given society requires a great deal of administrative competence to prevent intense social destabilisation (Tõnnison, 2004).…”
Section: Local Governments In Estoniamentioning
confidence: 99%